Associations of sleep duration and fruit and vegetable intake with the risk of metabolic syndrome in Chinese adults. Issue 10 (12th March 2021) - Wang, Ming-hui; Shi, Tong; Li, Qiang; Chen, Hong-Mei; Liu, Ming-wei; Lu, Yuan-an; He, Qiqiang; Chen, Rui
Abstract : Abstract: To understand the adverse association of short sleep duration and insufficient fruit and vegetable intake (FVI) with and their combined effect on metabolic syndrome (MetS) in Chinese adults. This cross-sectional study analyzed 7052 adults aged 18∼64 years old in 2009, with fasting blood samples collected. Participants were divided into short/normal/long sleep duration groups and sufficient/insufficient FVI groups in accordance with self-reported information. Metabolic syndrome was defined by National Cholesterol Education Program's Adult Treatment Panel III criteria. The prevalence of MetS among the study subjects was 21.74%. Participants were classified into short (<7 h/d), normal (7∼9 h/d), and long (>9 h/d) groups according to their daily sleep duration. Participants with less than 500 g of FVI per day was considered as insufficient FVI. After adjusting for confounders, the negative effect of short sleep duration on MetS was statistically significant, with an OR of 1.29 (95%CI = 1.06∼1.56); and high fasting glucose levels were significantly associated with insufficient FVI. Compared with subjects with normal sleep duration and sufficient FVI, participants with short sleep time and insufficient FVI had the highest risk of MetS (OR = 1.37, 95% CI: 1.04–1.66). This study revealed that insufficient FVI and short sleep duration were significantly associated with an increased risk of MetS among Chinese adults. Increasing FVI and normal sleep duration during Chinese adults could be significant targets for reducing the prevalence of MetS.